2020
DOI: 10.3390/biom10040658
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Selenoproteins in Adipose Tissue Physiology and Obesity

Abstract: Selenium (Se) homeostasis is tightly related to carbohydrate and lipid metabolism, but its possible roles in obesity development and in adipocyte metabolism are unclear. The objective of the present study is to review the current data on Se status in obesity and to discuss the interference between Se and selenoprotein metabolism in adipocyte physiology and obesity pathogenesis. The overview and meta-analysis of the studies on blood Se and selenoprotein P (SELENOP) levels, as well as glutathione peroxidase (GPX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 262 publications
(261 reference statements)
2
40
0
3
Order By: Relevance
“…Furthermore, several studies indicate that Se levels are lower in obese individuals and a recent systematic review confirmed both that mean levels of Se in blood/serum were lower in the obese compared with healthy adult subjects and that mean blood GPX activity was decreased in obese individuals (96) . Interestingly, the authors reported that Se levels were higher in subjects with the metabolic syndrome.…”
Section: Selenium Status and Covid-19mentioning
confidence: 90%
“…Furthermore, several studies indicate that Se levels are lower in obese individuals and a recent systematic review confirmed both that mean levels of Se in blood/serum were lower in the obese compared with healthy adult subjects and that mean blood GPX activity was decreased in obese individuals (96) . Interestingly, the authors reported that Se levels were higher in subjects with the metabolic syndrome.…”
Section: Selenium Status and Covid-19mentioning
confidence: 90%
“…It is well established that adequate levels of selenium are important for the functioning of the central nervous system, endocrine system, reproductive system, and cardiovascular system, as well as for regulating immune processes [ 23 ]. A very recent review of the literature on Se metabolism in adipocyte physiology and obesity pathogenesis concluded that Se appears to play an essential role in adipose tissue physiology and pathophysiology, but strongly emphasized the huge inconsistency in the findings of studies on the human population [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In selenium deficiency, the action of GPs was greatly diminished and was associated with increased cardiovascular (CVD) incidence, some cancers and overall mortality. Additionally, selenium levels are usually reduced in obesity, with the subsequent reduction in expression of selonoprotein genes, further diminishing antioxidative properties and the immune response [ 68 ]. A new meta-analysis examined the role of selenium with and without antioxidant mixtures for the risk of CVD, cancers and mortality.…”
Section: Precision Nutrition For Osa and Lgci In Good Times And Inmentioning
confidence: 99%